The European Nucleotide Archive in 2018. Issue Volume 47:Issue D1(2019) (5th November 2018) - Harrison, Peter W; Alako, Blaise; Amid, Clara; Cerdeño-Tárraga, Ana; Cleland, Iain; Holt, Sam; Hussein, Abdulrahman; Jayathilaka, Suran; Kay, Simon; Keane, Thomas; Leinonen, Rasko; Liu, Xin; et al.
Abstract: The European Nucleotide Archive (ENA;https://www.ebi.ac.uk/ena ), provided from EMBL-EBI, has for more than three decades been responsible for archiving the world's public sequencing data and presenting this important resource to the scientific community to support and accelerate the global research effort. Here, we outline ENA services and content in 2018 and provide an overview of a selection of focus areas of development work: extending data coordination services around ENA, sequence submissions through template expansion, early pre-submission validation tools and our move towards a new browser and retrieval infrastructure.